Comparative study of the role of pronator quadratus repair versus no pronator quadratus repair in volar plate fixation of distal radius fractures - Kumar, Shubham; Choudhary, Rakesh; Rahman, Shamir (International Journal of Research in Orthopaedics, 2025)
Background: There is a controversy regarding the merits of repairing pronator quadratus (PQ) following volar plate fixation of distal radius fracture via Henry’s approach. The aim of this study was to evaluate and compare the post-operative functional outcome between those with PQ repair vs those without PQ repair. Methods: The 41 patients (33 males and 8 females) were included in this randomized controlled trial as per our inclusion and exclusion criteria. Of these 21 patients were in group A in which PQ repair was done and 20 patients were in group B in which PQ repair was not done. Both groups were compared with DASH score, wrist range of motion, post-operative pain and grip strength. Results: The patients were followed up for minimum 1 year. Patients in both the groups shared similar baseline and demographic characteristics. There was no significant difference in the mean DASH score and mean grip strength at any point of time in follow up. However, wrist flexion at 6 weeks was better in group A (p=0.03) along with post-operative pain at 2nd and 6th week (p=0.035, 0.039). Conclusions: PQ repair during volar plating of distal radius fractures does not provide any significant better functional outcome, range of motion and grip strength, especially in long run. But it reduced early post-operative pain significantly.